PERCEPCIÓN DE LOS USUARIOS DEL SERVICIO DE TRANSPORTE TREN, COSTA RICA, MAYO DE 2012 - Abarca Rodríguez, Allan (2013)
The increased growth of the vehicle fleet and the lack of road infrastructure improvement in Costa Rica have generated not only a policy of reactivation of the transportation services by train, but also the rising need to extend routes. This article is a product of a research on the users’ perception of a specific train route connecting two provinces, San José and Heredia. 396 users of the service were interviewed, who in general terms described the service as very satisfactory. They demand, nonetheless, the extension of routes and trips, as well as an improvement on the access infrastructure.